PRICE VOLATILITY AND SPILLOVER OF BIG CAYENNE (Capsicum annuum L.) IN MALANG DISTRICTS - Nurul Khabibah; Ratya Anindita; Wiwit Widyawati (Agricultural Socio-Economics Journal, 2019)
Production of big cayenne in Malang Districts has trend increase while consumption has trends decrease make excess supply. Unbalanced supply and demand causes price fluctuation between producers and consumers. Price fluctuations can pose risks and price uncertainties or price changes known as price volatility. The purpose of this research is to analyze price volatility that occurs at the level of producers and consumers of big cayenne in Malang Districts, and analyze the spillover volatility that occurs at the price of producers and consumers big cayenne in Malang Districts. The method used to analyze price volatility is ARCH/GARCH models and the method used to analyze the spillover volatility is EGARCH models. The results showed that the price volatility of big cayenne in Malang Regency at the producer and consumer level is low volatility and the results of spillover volatility showed that the price of big cayenne producers and consumers in Malang Districts occur spillover volatility.